Serum concentrations of laminin in cirrhosis of the liver. Issue 7 (July 1993) - Collazos, J; Díaz, F; Genollá, J
Abstract : Laminin, a glycoprotein synthesised by Ito cells, has been considered a marker of fibrogenesis. The behaviour of laminin and clinical and laboratory data in 83 patients with cirrhosis were studied to find the factors associated with increases in this glycoprotein. There were increased concentrations of laminin in 62.7% of the patients (40% of the Child's A, 64.5% of the Child's B, and 75% of the Child's C categories). Significant differences in laminin concentrations were found between the Child's grades (p = 0.009) and between patients and controls (p < 0.0001). Correlations were found between laminin concentrations and mean corpuscular volume, aspartate aminotransferase, aspartate aminotransferase: alanine aminotransferase ratio, alkaline phosphatase activity, bilirubin and glycocholic acid concentrations, and hypoalbuminaemia--that is, variables related to liver insufficiency and alcohol intake. Moreover, patients with an alcohol intake higher than 100 g/day had higher laminin concentrations than those with a lower intake (p = 0.03). Conversely, there was no significant association with portal hypertension. Multivariate analysis showed that mean corpuscular volume, bilirubin concentrations, and hypoalbuminaemia were independently associated with laminin concentrations. Poor degradation associated with liver insufficiency seems to play an important part in the increase in serum laminin concentrations in these patients.